Anatomy of a range contraction: Flow–phenology mismatches threaten salmonid fishes near their trailing edge - Stephanie M. Carlson; Kasey C. Pregler; Mariska Obedzinski; Sean P. Gallagher; Suzanne J. Rhoades; Cleo Woelfle-Hazard; Nathan Queener; Sally E. Thompson; Mary E. Power (Proceedings of the National Academy of Sciences, 2025)
Climate change is redistributing life on Earth, with profound impacts for ecosystems and human well-being. While repeat surveys separated by multidecadal intervals can determine whether observed shifts are in the expected direction (e.g., poleward or upslope due to climate change), they do not reveal their mechanisms or time scales: whether they were gradual responses to environmental trends or punctuated responses to disturbance events. Here, we document population reductions and temporary range contractions at multiple sites resulting from drought for three Pacific salmonids at their ranges’ trailing edge. During California’s 2012 to 2016 historic multiyear drought, the 2013 to 2014 winter stood apart because rainfall was both reduced and delayed. Extremely low river flows during the breeding season (“flow–phenology mismatch”) reduced or precluded access to breeding habitat. While Chinook ( Oncorhynchus tshawytscha) experienced a down-river range shift, entire cohorts failed in individual tributaries (steelhead trout, O. mykiss ) and in entire watersheds (coho salmon, O. kisutch) . Salmonids returned to impacted sites in subsequent years, rescued by reserves in the ocean, life history diversity, and, in one case, a conservation broodstock program. Large population losses can, however, leave trailing-edge populations vulnerable to extinction due to demographic stochasticity, making permanent range contraction more likely. When only a few large storms occur during high flow season, the timing of particular storms plays an outsized role in determining which migratory fish species are able to access their riverine breeding grounds and persist.